A biphenyl containing two electron-donating and two electron-accepting moieties: a rigid and small donor–acceptor–donor ladder system. Issue 11 (5th January 2016) - Greulich, Tobias W.; Suzuki, Naoya; Daniliuc, Constantin G.; Fukazawa, Aiko; Yamaguchi, Eriko; Studer, Armido; Yamaguchi, Shigehiro
Abstract : A small ladder-type donor–acceptor–donor π-system, a biphenyl furnishing two phosphine oxide bridges and two amino groups, showed significantly red-shifted absorption and fluorescence. Abstract : Ladder π-conjugated materials and also push–pull systems belong to important classes of compounds for the development of organic electronic devices. In this communication, a novel π-conjugated material that unifies the properties of both of these classes is presented. The material comprises a rigid biphenyl framework, which bears two bridging electron-accepting phosphine oxide moieties as well as two electron-donating amino groups. The structure and photophysical properties of this compound are discussed and compared with those of a related system lacking the second P-moiety.